Pre-treatment of lignocellulosic biomass: review of various physico-chemical and biological methods influencing the extent of biomass depolymerization - Baksi, S.; Saha, D.; Saha, S.; Sarkar, U.; Basu, D.; Kuniyal, J. C. (International journal of environmental science and technology (Tehran), 2023)
Pre-treatment of biomass is a necessary step for delignification as well as an unavoidable step in the journey of biomass to biofuel. Apart from delignification, defragmentation and partial depolymerization of biomass are two other additional useful steps in the overall process of pre-treatment. Ultimately these three steps together make the downstream enzymatic hydrolysis process more effective in producing optimum total reducing sugar. Several different pre-treatment technologies are available to delignify various types of biomasses with each of them being unique concerning specific advantages and disadvantages, characteristics of its own. However, different pre-treatment methods, in combination, have been found beneficial with higher delignification efficiency in comparison to a single pre-treatment method, implemented on its own. Apart from physical pre-treatment procedures like milling, grinding, steam explosion, etc., pre-treatment methods can be divided, roughly, into three groups: biological pre-treatment, physical pre-treatment and chemical pre-treatment. Chemical pre-treatments always arrest significantly higher attention due to their effectiveness and minimum treatment time required. In this review, a thorough discussion of various chemical and biological pre-treatment technologies, along with their efficacy and effective outcomes, have been discussed in order to understand their impacts on bioenergy industries. Graphical abstract